The Mental Health of Patients With Psychotic Disorder From a Positive, Multidimensional and Recovery Perspective - Broncano-Bolzoni, Miriam; González-Carrasco, Mònica; Juvinyà-Canal, Dolors; Lluch-Canut, MTeresa (Frontiers in Psychology, 2022)
Positive mental health (PMH) and mental illness are distinct, yet interrelated, constructs. However, this relationship has yet to be adequately established. We aimed to evaluate the level of PMH and its relationship with sociodemographic and clinical determinants as well as to explore the relationship between PMH and the positive constructs of recovery, subjective well-being (SWB), insight and functioning in patients with psychotic disorder. A multicenter, descriptive, cross-sectional and correlational study with a sample of 347 patients with psychotic disorder was conducted. The following assessment instruments were used: Positive Mental Health Questionnaire, Maryland Assessment of Recovery in Serious Mental Illness scale, Insight Scale, Personal Wellbeing Index-Adult version (PWI-A), Overall Life Satisfaction (OLS) and Global Assessment of Functioning scale. The mean global level of PMH was 116.16 (range of 39-156, SD = 19.39). Significant differences were found in PMH in relation to sociodemographic (sex, civil status and employment situation) and clinical variables (family history of mental disorders, number of prescribed antipsychotics, treatment with anxiolytics, treatment with antidepressants and suicide attempts). PMH was significantly and positively correlated with recovery (r = 0.760), SWB (PWI-A: r = 0.728 and OLS: r = 0.602) and functioning (r = 0.243), and negatively with insight (r = -0.335). These results can lead to a major change in mental health care. If actions are taken to increase PMH, then recovery, SWB and functioning will also increase. At the same time, interventions should be carried out to boost insight, since increasing PMH could decrease insight, all resulting in better quality of life for patients with psychotic disorder.